2013
DOI: 10.1175/jcli-d-12-00264.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation and Spatial Patterns of the Atmospheric Component of the Pacific Decadal Oscillation

Abstract: The Pacific decadal oscillation (PDO) is an El Niño–Southern Oscillation (ENSO)-like climate oscillation that varies on multidecadal and higher-frequency scales, with a sea surface temperature (SST) dipole in the Pacific. This study addresses the seasonality, vertical structure, and across-variable relationships of the local North Pacific and downstream North American atmospheric signal of the PDO. The PDO-based composite difference fields of 500-mb geopotential height, surface air temperature, sea level press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…Previous studies suggested that the PDO would have little direct impact on precipitation and temperature over the southwest United States but can have indirect influences on the regions through the modulation of ENSO effects or other internal variability of the midlatitude atmosphere (Gershunov and Barnett 1998;McCabe and Dettinger 1999;Mo et al 2009;Mills and Walsh 2013;Newman et al 2016). For example, a recent study by Liu et al (2016) found that the PDO can influence California precipitation through the modification of the frequency and intensity of atmospheric rivers (ARs), a large-scale process that is often linked to extreme rainfall events in California.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that the PDO would have little direct impact on precipitation and temperature over the southwest United States but can have indirect influences on the regions through the modulation of ENSO effects or other internal variability of the midlatitude atmosphere (Gershunov and Barnett 1998;McCabe and Dettinger 1999;Mo et al 2009;Mills and Walsh 2013;Newman et al 2016). For example, a recent study by Liu et al (2016) found that the PDO can influence California precipitation through the modification of the frequency and intensity of atmospheric rivers (ARs), a large-scale process that is often linked to extreme rainfall events in California.…”
Section: Introductionmentioning
confidence: 99%
“…The PDO and NPGO signals can affect the weather and climate over the North Pacific, East Asia, and North America on decadal time scales. In addition, they can influence the local weather and climate indirectly through modulating interannual variability such as El Niño-Southern Oscillation (ENSO; Alexander et al 2002;Mantua and Hare 2002;Zhu and Yang 2003a,b;Yang et al 2004;Chan and Zhou 2005;Zhou et al 2006;Linkin and Nigam 2008;Ceballos et al 2009;Di Lorenzo et al 2010;Furtado et al 2012;Mills and Walsh 2013;Zhu et al 2014). Moreover, natural decadal variability is of critical importance to climate prediction for the next few decades (Meehl et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The variations in climate over the AP on both interannual and interdecadal scales were recognized to be predominantly affected by the ENSO (Deser, Phillips, and Hurrell 2004) and Arctic Oscillation/North Atlantic Oscillation (Nitta and Yamada 1989;Battisti 1997, 1998;Enfield and Mestas-Nuñez 1999;Newman, Gilbert, and Michael 2003;Mills and Walsh 2013;Patterson et al 2013). To explore the drivers of trends and variability in vegetation dynamics over the AP we therefore compared and calculated the correlation between the annual NDVI and the standardized values for the PDO index and ENSO.…”
Section: Resultsmentioning
confidence: 99%
“…The PDO-based composite difference fields of surface air temperature and precipitation vary not only across seasons, but also from one calendar month to another within a season, although monthto-month continuity is apparent (Mills and Walsh 2013). In the AP region, the PDO is an ENSO-like On the pixel level, the 30-year linear trends for individual vegetation dynamic indicators were first calculated and a t test was used to test the significance and a p value <.05 was considered significant.…”
Section: Resultsmentioning
confidence: 99%